15‐Deoxy‐Δ12, 14‐prostaglandin J2 binds and inactivates STAT3 via covalent modification of cysteine 259 in H‐Ras‐transformed human breast epithelial cells. Issue 5 (8th February 2021) - Kim, Su‐Jung; Cho, Nam‐Chul; Han, Bitnara; Kim, Kyeojin; Hahn, Young‐Il; Kim, Kwang Pyo; Suh, Young Ger; Choi, Bu Young; Na, Hye‐Kyung; Surh, Young‐Joon
Abstract : Signal transducer and activator of transcription 3 (STAT3) has been considered as a potential target for development of anticancer therapeutics. Here, we report a novel mechanism by which the cyclopentenone prostaglandin, 15‐deoxy‐Δ 12, 14 ‐prostaglandin J2 (15d‐PGJ2 ) functions as an allosteric inhibitor of STAT3. 15d‐PGJ2 inhibits phosphorylation, dimerization, nuclear translocation, and transcriptional activity of STAT3 in H‐ Ras ‐transformed human mammary epithelial cells (MCF10A‐ Ras ) through the Michael addition reaction at cysteine 259 of STAT3. Comparative studies with 15d‐PGJ2 analogues reveal that both C12‐C13 and C9‐C10 double bonds conjugated to the carbonyl group in the cyclopentenone ring of 15d‐PGJ2 are essential for STAT3 binding. Antiproliferative and pro‐apoptotic activities of 15d‐PGJ2 in MCF10A‐ Ras cells are attributable to covalent modification of STAT3 on Cys259, and mimic the effects induced by mutation of this amino acid. Abstract :